2007
DOI: 10.1016/j.abb.2006.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Pentalenolactone biosynthesis: Molecular cloning and assignment of biochemical function to PtlF, a short-chain dehydrogenase from Streptomyces avermitilis, and identification of a new biosynthetic intermediate

Abstract: Pentalenolactone (1) is an antibiotic that has been isolated from many species of Streptomyces. The putative dehydrogenase encoded by the ptlF gene (SAV2993) found within the Streptomyces avermitilis pentalenolactone gene cluster was cloned and overexpressed in Escherichia coli. PtlF, which belongs to the short-chain dehydrogenase/oxidoreductase superfamily, was shown to catalyze the oxidation of 1-deoxy-11β-hydroxypentalenic acid (9) to 1-deoxy-11-oxopentalenic acid (10), a new intermediate of the pentalenola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 24 publications
0
27
0
Order By: Relevance
“…CYP117 falls into class II/class E (subgroup IV) within the CYP superfamily, which archetypically have a two-component electron transfer system in which an NADPH-cytochrome P450 reductase (CPR) directly supplies electrons to the CYP 22 , although in several cases it has been demonstrated that such CYPs can be reduced by the more typical bacterial 3-component system 48,49 . CYP114 and CYP112 belong to class B of the CYP superfamily.…”
Section: Methodsmentioning
confidence: 99%
“…CYP117 falls into class II/class E (subgroup IV) within the CYP superfamily, which archetypically have a two-component electron transfer system in which an NADPH-cytochrome P450 reductase (CPR) directly supplies electrons to the CYP 22 , although in several cases it has been demonstrated that such CYPs can be reduced by the more typical bacterial 3-component system 48,49 . CYP114 and CYP112 belong to class B of the CYP superfamily.…”
Section: Methodsmentioning
confidence: 99%
“…Recombinant 1-deoxy-11β-hydroxypentalenic acid dehydrogenase (PtlF) was expressed and purified as previously described (45). Restriction enzymes and T4 DNA ligase were purchased from New England Biolabs and used according to the manufacturer’s specifications.…”
Section: Methodsmentioning
confidence: 99%
“…11, 44, 45 The recombinant 1-deoxy-11β-hydroxypentalenic acid dehydrogenase PtlF was prepared as described previously. 45 The sample of 3 (0.1 mM) was incubated at room temperature with recombinant PtlF (14.4 μM) and β-NAD + (1.6 mM) in 1 mL of Tris buffer (100 mM Tris-HCl, 1.5 mM DTT, 2% DMSO, pH 8.0) to generate 4 . After 1 h, purified PntE or PntE mutant protein (1.7 μM) was added along with β-NADPH (1 mM) and FAD (50 μM).…”
Section: Methodsmentioning
confidence: 99%